Business Development Strategy With Swot and QSPM Methods (Case Study: Kampung Kopi Banaran) - Rida, Rizkha; Sanco Simanullang; Donni Syahrial; Zufri Hasrudy Siregar (PT Inovasi Pratama Internasional, 2026)
Kampoeng Kopi Banaran is one of the trademarks that has been established since 2003 in Bawen, Central Java, Indonesia. Kampoeng Kopi Banaran itself houses several business lines under it such as Banaran Sky View Restaurat and Banaran Coffee Shop. Banaran Coffee Shop is one of the business units of Kampoeng Kopi Banaran which has been established since 2003 until now. To achieve this desire, of course, the Kampoeng Kopi Banaran must understand the right strategy so that the business carried out can be well accepted in the market. This research uses three interrelated data processing methods, namely the IFE and EFE matrices, IE matrices, SWOT matrices and QSPM matrices. The IFE and EFE matrices are used to analyze internal and external factors, the SWOT and IE matrices are used to determine alternative development strategies for Kampoeng Kopi Banaran and the QSPM method is used to determine the priority of the Kampoeng Kopi Banaran strategy. The Strengths-Opportunities strategy, which involves using strengths to seize opportunities through different approaches, is the best company development plan for Kampoeng Kopi Banaran. a. Support from Influencers b. Make use of social media and produce engaging and pertinent material for customers. The Integration of methods create an objective and measurable strategies successfully.